User Interface Design for DIVAYANA Evaluation Application Based on Positive-Negative Discrepancy - Divayana, Dewa Gede Hendra; Suyasa, P. Wayan Arta; Ariawan, I Putu Wisna; Mariani, Ni Wayan Rena; Sugiharni, Gusti Ayu Dessy; Gama, Adie Wahyudi Oktavia (Journal of Applied Data Sciences, 2023)
This study aims to show the user interface design form of the DIVAYANA evaluation application based on Positive-Negative Discrepancy. The method in this research is a development method that uses the Borg and Gall model. The development refers to the design stage, initial design trials, and revisions to initial design trials. Tests on user interface design involved 104 respondents. The instrument was a questionnaire consisting of 15 questions. Analysis of the trial data used a quantitative descriptive technique. The results of the study show that the quality of the user interface design is quite good. The impact of the results of this research on educational evaluators is that there is new knowledge about the existence of a user interface design that is important to know to support the realization of physical quality evaluation applications.